Review Article. Issue 1 (1st May 2019) - Conrich, Ian
Selling the Dream: The Art of Early New Zealand Tourism, Peter Alsop, Gary Stewart and Dave Bamford (2013) Nelson: Craig Potton Publishing, 408pp., ISBN 978 1 87751 777 8 (hbk), NZ79.99Promoting Prosperity: The Art of Early New Zealand Advertising, Peter Alsop and Gary Stewart (2013) Nelson: Craig Potton Publishing, 440pp., ISBN 978 1 87751 796 9 (hbk), NZ79.99